Enhancing SMEs Business Performance Through Strategic Digital Transformation - Magda Siahaan; Sandy Kosasi; Nengah Sukendri; Abigail Husain (Pandawan Sejahtera Indonesia, 2025)
This study examines the role of digital transformation strategies in enhancing business management practices within Small and Medium Enterprises (SMEs) in Tangerang, Indonesia. SMEs in this region face ongoing challenges in adopting digital technologies, including limited financial resources, inadequate digital skills, and internal resistance to change, while increasing competition and rapid technological advancement demand adaptation to remain competitive. The purpose of this research is to analyze how digital transformation strategies cloud computing, digital marketing, automation, and data analytics affect business outcomes such as operational efficiency, customer engagement, and market competitiveness. A quantitative approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on survey data from 150 SMEs actively implementing digital initiatives in Tangerang. The findings show that cloud computing and data analytics significantly improve operational efficiency through workflow optimization and data-driven decision-making, while digital marketing and automation have a positive impact on customer engagement and competitive positioning. SMEs that adopt these strategies demonstrate enhanced management performance and stronger market responsiveness. The study offers empirical evidence supporting the strategic value of digital transformation for SMEs in emerging regions and highlights the importance of investment in digital capability building. These insights may guide SME leaders and policymakers in strengthening digital adoption to support sustainable economic development. Future research should incorporate longitudinal approaches to evaluate longterm impact and qualitative perspectives to better understand contextual challenges in digital transformation implementation.